Cariprazine augmentation in patients with treatment resistant unipolar depression who failed to respond to previous atypical antipsychotic add-on. A case-series - Pessina, Enrico; Martini, Azzurra; Raffone, Fabiola; Martiadis, Vassilis (Frontiers in Psychiatry, 2023)
Among individuals receiving an adequate pharmacological treatment for Major Depressive Disorder (MDD), only 30% reach a full symptom recovery; the remaining 70% will experience either a pharmacological response without remission or no response at all thus configuring treatment resistant depression (TRD). After an inadequate response to an antidepressant, possible next step options include optimizing the dose of the current antidepressant, switching to a different antidepressant, combining antidepressants, or augmenting with a non-antidepressant medication. Augmentation strategies with the most evidence-based support include atypical antipsychotics (AAs). Few data are available in literature about switching to another antipsychotic when a first augmentation trial has failed. We present a case-series of patients with unipolar treatment resistant depression who were treated with a combination of antidepressant and low dose of cariprazine after failing to respond to a first augmentation with another AA. We report data about ten patients affected by unipolar depression, visited at the outpatients unit of Mental Health Department of ASL CN2 of Bra and NA1 of Napoli (Italy). All patients failed to respond to conventional antidepressant therapy. A low dose of AA (aripiprazole, risperidone or brexpiprazole) was added for one month to the ongoing antidepressant treatment without clinical improvement. A second augmentation trial was then made with cariprazine. Seven out of ten patients were responders at the end of period, of them 1 patient reached responder status by week 2. HAM-D mean scores decreased from 23.9 ± 3.9 (baseline) to 14.8 ± 5.3 (4 weeks). Cariprazine was well tolerated, no severe side effect was observed during the trial. Our sample of treatment resistant unipolar patients showed good response to augmentation with cariprazine. Failure to a first AA-augmentation trial does not preclude response to a second one. This preliminary result requires confirmation through more rigorous studies conducted over greater samples.